Gestational Diabetes in the United States: Temporal Changes in Prevalence Rates Between 1979 and 2010. Issue 1 (March 2018) - Lavery, J.A.; Friedman, A.M.; Keyes, K.M.; Wright, J.D.; Ananth, C.V.
Abstract : ( BJOG . 2017;124:804–813) Gestational diabetes mellitus (GDM) is one of the most common conditions complicating pregnancy, affecting an estimated 8.3% of pregnancies worldwide and 3% to 4% of pregnancies in the United States. Not only are women with GDM more likely to develop type-II diabetes later in life, but they are also at increased risk for preeclampsia and gestational hypertension in subsequent pregnancies. As a result of women with pregnancies complicated by GDM being more likely to have large for gestational age (LGA) infants, they have an increased risk of being delivered via cesarean section and or suffering birth injury.